PEMBELAJARAN BERDIFERENSIASI PADA MATA PELAJARAN PAI DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA KELAS IV UPTD SDN GUNUNG SEKAR 1 SAMPANG - Delvi Serica Kulzum; Waqiatul Masrurah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The low learning motivation of students in Islamic Religious Education could not be separated from the differences in students’ abilities, interests, and learning needs. This condition encouraged teachers to implement differentiated learning so that the learning process would be more aligned with students’ characteristics in the classroom. This study aimed to describe the implementation of differentiated learning and to examine the changes in the learning motivation of fourth-grade students at UPTD SDN Gunung Sekar 1 Sampang. The research applied a descriptive qualitative approach, while the data were collected through observation, interviews, and documentation involving Islamic Religious Education teachers, the principal, and fourth-grade students. The collected data were then analyzed through data reduction, data presentation, and conclusion drawing. The findings indicated that the implementation of differentiated learning had a positive impact on students’ learning motivation. Teachers adjusted teaching methods, learning media, and classroom activities according to students’ learning needs, which encouraged students to participate more actively in the learning process. In addition, students appeared more confident in expressing their opinions and showed greater enthusiasm during Islamic Religious Education lessons. The classroom atmosphere also became more interactive, helping students understand the material more effectively and reducing boredom during the learning process.